Adsorción de mercurio y cadmio en carbón subbituminoso oxidado-xantado, sulfonado o activado y resina sintética comercial (2015)
The combustion of low rank coal produces environmental impacts due to its low heat of combustion and high heteroatom content which has promoted its alternative uses as an adsorbent. A subbituminous coal (CS) was oxidized with air at 150°C on a fixed bed for 4 hours and xanthated with carbon disulfide in a basic solution, at 30°C. The resulting xanthated coal (CX) was evaluated for the adsorption of Hg2+ and Cd2+ from 0,100, 1,000, 12.48, 124.8 y 998.3mg/L aqueous solutions; metal concentrations were determined by atomic absorption spectrometry. CX was compared against CS, a sulfonated CS, activated CS (CAp), a commercial activated carbon (CAC), and a commercial synthetic resin (RC) in terms of Hg2+ and Cd2+ adsorption. RC showed the highest adsorption capacity (concentration factor 98%) followed by theCX (concentration factor 96%). The adsorption of cadmium on the sulfonated CS was 0.56meq/g, lower than that of CX, 1.85meq/g. In general, Hg2+ was less adsorbed than Cd2+; the adsorption capacities decreased in the order: RC, CX, sulfonated CS, activated CS, CS, and CAC. CX showed a better Cd2+ adsorption, 81% against 15%, than a non-oxidized 40-hours-xanthated coal, which shows that oxidation of coal increased the amount of oxygenated groups that enhanced xanthation.